2021
DOI: 10.1002/ps.6298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flupyradifurone for the management of the Asian citrus psyllid Diaphorina citri via dripping irrigation systems

Abstract: BACKGROUND Chemical control is the most used and effective method to control Diaphorina citri, the vector of the phloem‐limited bacteria associated with citrus huanglongbing (HLB) disease. The objectives of this study were to determine the effectiveness of flupyradifurone applied via dripping irrigation systems on D. citri. Bioassays were conducted using leaves harvested on various dates post treatment, and insecticide residue in leaf tissue was quantified. RESULTS The drip application of flupyradifurone on ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Eurycomanone (EN), an active compound from the root of Eurycoma longifolia Jack, was isolated in our previous study . EN showed a 1.8-times stronger antimalarial activity than chloroquine and good inhibitory activity against various tumor cells, including Caov-3, HeLa, Hep G2, HM3KO, and MCF-7, but showed no toxicity to normal human cells. , Our studies further confirmed that EN had significant antifeedant and growth inhibitory activities against various lepidopteran pests such as Spodoptera litura, Spodoptera frugiperda, Plutella xylostella, and Spodoptera exigua and had good plant systemic properties. , Systemic pesticides could be absorbed by crop leaves or roots and transported to the target sites of pests through the phloem, which not only solves the problem of the potential difference between the spraying site and the pest feeding site but also effectively reduces the time of contact of the active ingredient with light and could prolong the field duration period and improve the control effect . EN has shown broad development and application prospects in the prevention and control of lepidopteran pests, although the molecular mechanism of EN toxicity is not clear.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Eurycomanone (EN), an active compound from the root of Eurycoma longifolia Jack, was isolated in our previous study . EN showed a 1.8-times stronger antimalarial activity than chloroquine and good inhibitory activity against various tumor cells, including Caov-3, HeLa, Hep G2, HM3KO, and MCF-7, but showed no toxicity to normal human cells. , Our studies further confirmed that EN had significant antifeedant and growth inhibitory activities against various lepidopteran pests such as Spodoptera litura, Spodoptera frugiperda, Plutella xylostella, and Spodoptera exigua and had good plant systemic properties. , Systemic pesticides could be absorbed by crop leaves or roots and transported to the target sites of pests through the phloem, which not only solves the problem of the potential difference between the spraying site and the pest feeding site but also effectively reduces the time of contact of the active ingredient with light and could prolong the field duration period and improve the control effect . EN has shown broad development and application prospects in the prevention and control of lepidopteran pests, although the molecular mechanism of EN toxicity is not clear.…”
Section: Introductionsupporting
confidence: 70%
“…17,21 Systemic pesticides could be absorbed by crop leaves or roots and transported to the target sites of pests through the phloem, which not only solves the problem of the potential difference between the spraying site and the pest feeding site but also effectively reduces the time of contact of the active ingredient with light and could prolong the field duration period and improve the control effect. 22 EN has shown broad development and application prospects in the prevention and control of lepidopteran pests, although the molecular mechanism of EN toxicity is not clear. Studying the toxicological mechanism of EN in S. frugiperda will provide a scientific basis for the development and utilization of EN and is also of great practical significance for the research and development of new and green target pesticides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The larvae mortality % in 1 st and 2 nd sprays were found more or less comparable with the work of (Lewis et al 2011), they recorded 100% LBF larvae mortality % when they were given treated leaves of methionine human nutrient amino acid and observed the positive effect on the larvae amino acid modulated system. Against the larvae of LBF the Helmet insecticide in proved more effective in 3 rd spray as described (Wen et al 2021), reported 50% and 80% mortality of Diaphorina citri at LC50 and LC80 dosages of flupyradifurone insecticide. The larvae mortality % in 1 st and 2 nd sprays are comparable with the result of (Butani, 1979), sprayed with monocrotophos 0.04 % and chlorpyriphos 0.05 % and at the rate of twenty litters per tree applied 0.04% phosphamidon and observed effects.…”
Section: Discussionmentioning
confidence: 92%
“…Improving the pesticide application methods is an effective approach to solving the issues caused by excessive agrochemical usages, such as non‐target impacts and pesticide residues 1–3 . Root application of pesticides through seed treatment or drip irrigation is an effective strategy that can enhance utilization efficiency, prolong the effective duration of pesticides, and increase water productivity by avoiding pesticide drift into the environment 4–6 . However, current systemic agrochemicals can contaminate crop parts consumed by vertebrates and pollinators attributable to their non‐controlled mobility within the plant.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Root application of pesticides through seed treatment or drip irrigation is an effective strategy that can enhance utilization efficiency, prolong the effective duration of pesticides, and increase water productivity by avoiding pesticide drift into the environment. [4][5][6] However, current systemic agrochemicals can contaminate crop parts consumed by vertebrates and pollinators attributable to their non-controlled mobility within the plant. Therefore, the development of pesticides with vectorized translocation in crops is crucial.…”
Section: Introductionmentioning
confidence: 99%